CREATING ONLINE LEARNING ENVIRONMENTS FOR LANGUAGE ACQUISITION - Ibrayeva (Ибраева), Мeruyert (Меруерт) ("МӘҢГІЛІК ЕЛДІҢ МӘҢГІЛІК ТІЛІ" Халықаралық симпозиум материалдары/ THE ETERNAL LANGUAGE OF THE ETERNAL NATION international symposium, 2016)
Using online technologies in teaching and assessing the language is considered to be effective education. For effective assessment, creating online testing materials is a recognized method in higher education aimed at engaging students in effectively learning the language. Мақалада тіл үйрету мен бағалау үдерісінде пайдаланылатын онлайн технологиялардың артықшылықтары мен қиындықтары қарастырылады.
Keywords: language policies; language; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics